Integrated approach to predict the performance of nonlinear form of kenaf hybrid composite for construction application - Kiani, Golnar (2012)
The construction industry is not adapted for producing modern nonlinear dynamic forms of building designs. Prearranged machines and molding systems draw a lot of limitations to architects while designing. On the other hand, complex structural forms for these styles with their time consuming erecting and obscure nature prevent the designers to get involved in this challenge. Hence, it appears that the development in the building industry does not coincide with the architectural style of today. In order to overcome this inconsistency, this study aimed to define the criteria in the path of adopting the latest advanced system of other industries by means of rapid manufacturing and overcome one of the difficulties to achieve this goal. As this advanced system is not based on molding employment and is directly translating the design into production parts, the complexity of previous process will be automatically removed. This study firstly involved the defining of adoptable process stages and evaluating its criteria to be adopted into the construction industry. Secondly, the material specification and composition for the system and process as the chosen key-aspect was investigated. The investigation procedure was based on the latest literature review, experimental procedure and Ansys composite analysis. The selected fibre for the composition was Kenaf bast fiber. Lastly, defining the material workability as the load bearing component for the buildings using the advanced system of rapid manufacturing concept; which is extensively used in other industries to produce end products rather than prototyping called after Selective Laser Sintering, was investigated. This latest part utilized virtual simulation once more. The output of this system is a dramatic change for the current construction industry with its latest development. This system is called Rapid Manufacturing and is able to generate any complex form by fusing or sintering powdered bio-composite layer by layer governed by computer numerical control, until they reach the intended form and dimensions of designed prefab building components; consuming Kenaf based composite material. This effort successfully contributes to a new idea of enabling the use of the RM system into the construction industry simultaneously with its material needs announcement. Evaluating the system and material specifications through actual experiments are suggested for further study.